The Emergency Use of the oXiris Device with Continuous Kidney Replacement Therapy in COVID-19 Patients with Acute Kidney Injury - Raina, Rupesh; Mawby, Isabelle; Datla, Nikhil; Chakraborty, Ronith; Mehra, Kabir; Singh, Siddhartha; Agrawal, Nirav; Botsch, Alexander; Welko, Jeffrey; Neyra, Javier (Archives of Clinical and Biomedical Research, 2021)
Throughout the pandemic, presentations of the Coronavirus disease-2019 (COVID-19) infection have varied. Upon entering the body, SARS-CoV-2 causes a rapid release of pro-inflammatory cytokines and endotoxins, leading to multi-organ failure in intensive care unit (ICU) patients. In our case report, we present a 51-year-old male with severe COVID-19 infection in the ICU needing mechanical ventilation. He developed oliguric acute kidney injury (AKI) with acute respiratory distress syndrome and fluid overload >20% and was started on high flow continuous venovenous hemodiafiltration with oXiris filter via Prismaflex® (HF-CVVHDF). The patient received oXiris filter-based HF-CVVHDF for 72 hours and was switched to conventional CVVHDF. The patient gradually recovered with supportive care and was discharged. Through this case, we wish to highlight the significance of the use of an extracorporeal blood purification technology in COVID-19 with an oXiris filter to prevent morbidity and mortality among severe COVID-19 patients admitted to the ICU with AKI.